2016
DOI: 10.1016/j.scitotenv.2015.12.054
|View full text |Cite
|
Sign up to set email alerts
|

Direct contact between dust and HBCD-treated fabrics is an important pathway of source-to-dust transfer

Abstract: Hexabromocyclododecanes (HBCDs) are a class of brominated flame retardant that have found extensive application in consumer products used widely in indoor environments. Although uncertainty remains about the human health impacts of HBCDs, ingestion of HBCD-contaminated indoor dust has been shown to be a particularly significant exposure pathway for young children. Despite this, understanding of the mechanisms via which HBCD transfer from products to indoor dust remains incomplete. In this study, an in-house te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Direct transfer from materials (TV casings, textiles) to dust has been seen for BDE-209 and HBCDDs for example. 56,57 The TCEP (0.99 μg/g) and TDCIPP (2.6 μg/ g) concentrations were similar to those found in Wong et al's study (TCEP: 1.3 μg/g; TDCIPP: 1.9 μg/g), 35 but much lower than found in Bergh et al's study (TCEP: 7.0 μg/g; TDCIPP: 17 μg/g). 42 These results are consistent with the results found for the air samples, and support the hypothesis that this is due to the European phase out of some OPEs such as TCEP 58 and possible use shift to other FRs in Sweden.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
“…Direct transfer from materials (TV casings, textiles) to dust has been seen for BDE-209 and HBCDDs for example. 56,57 The TCEP (0.99 μg/g) and TDCIPP (2.6 μg/ g) concentrations were similar to those found in Wong et al's study (TCEP: 1.3 μg/g; TDCIPP: 1.9 μg/g), 35 but much lower than found in Bergh et al's study (TCEP: 7.0 μg/g; TDCIPP: 17 μg/g). 42 These results are consistent with the results found for the air samples, and support the hypothesis that this is due to the European phase out of some OPEs such as TCEP 58 and possible use shift to other FRs in Sweden.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
“…Interestingly, upholstery samples contained considerably higher concentrations than foam samples for HBCDD and BDE‐209. Both HBCDD and DecaBDE have had known applications as backcoating of fabrics used as furniture upholstery . This suggests that concentrations found in foam samples could be the result of BFR migration from flame‐retarded upholstery.…”
Section: Resultsmentioning
confidence: 99%
“…Schripp et al 40 conducted similar chamber studies but concluded that the migration of di-nbutylphthalate (DnBP) and DEHP from the source to dust may result from mass transfer between dust particles and the material's boundary layer. Recently, a few other chamber experiments have also been carried out to investigate the direct source-to-dust transfer of SVOCs, including phthalates, 41 polychlorinated biphenyls (PCBs), 42 polybrominated diphenyl ethers (PBDEs), 43 hexabromocyclododecanes (HBCDs), 44 and organophosphates. 45 However, although high levels of SVOCs in dust were commonly observed, these experiments could not demonstrate whether source-to-dust transfer occurred rapidly, what is the timescale for equilibrium to be reached, and what is the concentration level in dust at sorption equilibrium.…”
Section: ■ Introductionmentioning
confidence: 99%